Analysis of worker performances using statistical process control in fish paste otak-otak food industries - Sufa, Mila Faila; Ishak, Nazrul Iszhar; Rahim, M. Zulafif; Ibrahim, Mohd Rasidi (WARSE, 2019)
This research focuses on the improvement of Small and Medium Enterprises through the used of Process Statistical Control (SPC). An industry that focuses on the fish paste (known as “otak-otak”) production was taken as the case study in this research and the problems analysed are based on the real industrial experiences. The data collection for control charts were recorded for two weeks consisting of working time for each operator. The data were collected in subgroup of 16 with sample size of 5. The collection of data for weight of product was recorded randomly for the whole production line, while data collection of working time of operation was taken randomly from each operator every 30 minutes of the working hour. From this study, there are several problems had been detected in the process that been categories in six element that is people, method, measurement, machine, environment and materials. There were lack of motivation, lack of skill, lack of supervision, manual operation, lack of standard of procedure, waiting time in process, weight-based operator, lack of quality check, not using weight scale, conveyer that sometimes got stuck, spoon for tools, no automation, poor layout arrangement, talking while working, small working space, lack of hygiene, waiting time for material and easily spoiled. The findings can be used as the guideline to the industries for future production improvement. The industries would focus on elimination or reduction of the problems through their innovative solution.